Challenges for public transportation: Consequences and possible alternatives for the Covid-19 pandemic through strategic digital city application - Luis Andre Wernecke Fumagalli; Denis Alcides Rezende; Thiago André Guimar\~aes (Journal of Urban Management, 2021)
Public transport was already one of the biggest issues for all municipalities where people are highly concentrated at the same space at the same time. With COVID-19 pandemic and social distancing consequences, mass transportation is actually the main barrier for students and workers dependents of transport to go back to their daily routines with comfort and safety. Thus, the objective is to determine a demand control able to equalize the number of passengers in each car, respecting the COVID-19 social distancing protocols. The number of passengers in each time-of-day range were combined in four different models that included independent variables related to passenger's behavior indicating that almost 90% of all passengers are following a very strict and straight daily routine that can be coordinated and scheduled creating enough time space one from the other to avoid undesirable concentrations inside buses and bus stops. In conclusion, a very accurate urban management tool can arise from the study and may be able to solve not only the pandemic issues but also to improve local public services efficiency, to attract private investments and to improve citizen's quality of life.
Keywords: 710; COVID-19; Public transportation; Strategic digital city; Bus